THE INFLUENCE OF SOCIAL MEDIA ON YOUTH CONSCIOUSNESS - M. Misrbekova (The Conference Hub, 2025)
This article analyzes the influence of social media on youth consciousness from a scientific perspective. It explores aspects such as access to information, identity formation, moral values, and political socialization, highlighting both the positive and negative effects of these factors. The study is based on reliable academic sources and offers recommendations to promote conscious and responsible use of social media among youth.
Keywords: Social media, youth, consciousness, information, political socialization, mental health, values.